Squamous cell carcinoma predicts worse prognosis than adenocarcinoma in stage IA lung cancer patients: A population-based propensity score matching analysis - Hao, Bo; Li, Fang; Wan, Xiaoxia; Pan, Shize; Li, Donghang; Song, Congkuan; Li, Ning; Geng, Qing (Frontiers in Surgery, 2022)
Abstract Background: Although numerous studies have reported the association between histological types and the prognosis of ⅠA non-small lung cancer (NSCLC) patients, few studies deeply investigated the impact of pathology on the outcome of NSCLC patients. In this study, we comprehensively explored whether the type of histology influenced the outcome of ⅠA stage NSCLC patients. Methods: The study population was obtained from the Surveillance, Epidemiology, and End Results (SEER) Program, which is supported by the National Cancer Institute of the United States. To avoid potential bias, the method of propensity score matching (PSM) was used to obtain a balanced cohort for further analysis. Results: The results from univariate and multivariate regression models showed that lung squamous cell carcinoma (LSQCC) patients were at a significantly greater risk of undergoing shorter overall survival (OS). After PSM analysis, LSQCC was still closely associated with a reduction in OS and LCSS. All of these suggested that the histological type was an independent prognostic factor for OS and LCSS. Conclusion: Our study demonstrated that squamous cell carcinoma predicted worse OS and LCSS in ⅠA stage NSCLC patients compared to LUAD. We believe that the outcomes of LSQCC and LUAD are very different and that the two histological types should be differently analyzed.